2008
DOI: 10.1007/s12012-008-9022-2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Mediated Protection in Myocardial Ischemia-Reperfusion Injury

Abstract: Before menopause, a woman has a relatively low risk for developing cardiovascular disease. After menopause, however, the risk increases nearly twofold and cardiovascular disease remains the number one cause of death among women. Observational trials and studies in animal models of cardiovascular disease suggested that females have reduced injury after myocardial ischemia and reperfusion injury. However, two large clinical trials, the women's health initiative (WHI) and the heart estrogen and progestin replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 127 publications
6
33
0
1
Order By: Relevance
“…Our findings are also in accordance with those of previous studies that reported E2 to possess antioxidant activity because of its ability to bind to estrogen receptors and upregulate the expression of antioxidant enzymes through intracellular signaling pathways [9,[40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in accordance with those of previous studies that reported E2 to possess antioxidant activity because of its ability to bind to estrogen receptors and upregulate the expression of antioxidant enzymes through intracellular signaling pathways [9,[40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…A number of clinical and experimental studies confirmed that estrogen has beneficial effects on the cardiovascular system, particularly in myocardial I/R injury, atherosclerosis, and arrhythmia (Booth & Lucchesi 2008). Xin et al (2002) found that estrogen plays a protective role in the hypertrophic response of the heart to Ca 2C dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens have been demonstrated to reduce the extent of irreversible myocardial injury, ventricular arrhythmias and infarct size after I/R [167]. Non-transcriptional actions of estrogens in myocardial I/R have been suggested to be due to stimulation of NO production, inhibition of myocardial calcium accumulation, preservation of mitochondrial structure and function and antioxidant action [168][169][170].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Non-transcriptional actions of estrogens in myocardial I/R have been suggested to be due to stimulation of NO production, inhibition of myocardial calcium accumulation, preservation of mitochondrial structure and function and antioxidant action [168][169][170]. Interestingly, estrogens improve not only female but also male cardiac function after I/R [167]. Estradiol hormone in mitochondria can act on membranes directly or indirectly through estrogen receptors that have been identified in mitochondria [171].…”
Section: Antioxidantsmentioning
confidence: 99%